The first enantioselective total synthesis of the eremophilane-type sesquiterpenoid (-)-peniroqueforin C - Ingale, Sudhir R.; Vinodkumar, Ramavath; Kontham, Ravindar (Tetrahedron Letters, 2025)
Herein, we report the first stereoselective total synthesis of the eremophilane-type sesquiterpenoid (-)-peniroqueforin C using a chiral-pool strategy. This synthetic route features the use of readily available (S)-(+)-carvone as a chiral building block, Robinson annulation to construct the decalin system, substrate-controlled stereoselective methylation, single-step annulative construction of a tricyclic gamma-ylidene-butenolide with concomitant alkene transposition, and direct lactone-to-lactam conversion as key transformations.
Keywords: annulation reactions; Eremophilanes; Peniroqueforin C; Sesquiterpenoids; Total synthesis